A tale of two communities: intestinal polyparasitism among Orang Asli and Malay communities in rural Terengganu, Malaysia. Issue 1 (December 2016) - Elyana, Fatin; Al-Mekhlafi, Hesham; Ithoi, Init; Abdulsalam, Awatif; Dawaki, Salwa; Nasr, Nabil; Atroosh, Wahib; Abd-Basher, Mohamad; Al-Areeqi, Mona; Sady, Hany; Subramaniam, Lahvanya; Anuar, Tengku; et al.
Abstract Background Intestinal parasitic infections (IPIs) are still major health problems in many developing countries including Malaysia, particularly in the poor and socioeconomically deprived rural and remote communities in Peninsular Malaysia. This study was conducted to determine the prevalence of IPIs and to identify the key factors associated with intestinal polyparasitism as well as to evaluate the knowledge, attitude and practices (KAP) on IPIs among rural Orang Asli and Malay communities in Terengganu, Malaysia. Methods A cross-sectional study was conducted among 340 participants (165 Orang Asli and 175 Malay) aged ≤ 15 years from the Hulu Terengganu and Kemaman districts of Terengganu. Faecal samples were examined for the presence of intestinal parasites by using direct smear, formalin-ether sedimentation, trichrome stain, modified Ziehl Neelsen stain, in vitro cultivation in Jones' medium, Kato Katz and Harada Mori techniques. Demographic, socioeconomic, environmental and behavioural information of the participants and their KAP for IPIs were collected by using a pre-tested questionnaire. Results Overall, 149 (90.3 %) Orang Asli and 43 (24.6 %) Malay children were infected by at least one parasite species. The overall prevalences of intestinal polyparasitism among the Orang Asli and Malay were 68.5 % (113/165) and 14.3 % (25/175), respectively. Multiple logistic regression analysis showed that using unsafe water supply as a source for drinking water, the presence of domestic animals, not wearing shoes when outside, not washing vegetables before consumption, not washing hands after playing with soil, indiscriminate defecation and the low level of mother's education were the key risk factors for intestinal polyparasitism among the Orang Asli, while working mothers and the presence of domestic animals were the risk factors among the Malay children. Almost all the Malays were well aware about the IPIs while Orang Asli respondents had a poor level of related awareness. Conclusions This study demonstrates that IPIs are highly prevalent in rural Terengganu, Malaysia. Community awareness about IPIs was found to be imperative in protecting Malay children from these infections. An integrated control programme for the prevention and control of IPIs is highly recommended for these communities, with a special emphasis on the Orang Asli population.